Electronic Health Records interoperability in Peru - Alarcon-Loayza, Luis (2019)
Currently, our country is in a process of analysis and design for the implementation of an integrated repository of electronic medical records RENHICE by the Ministry of Health - MINSA, through which you can access the medical records of all patients, for this it is important to define how the exchange of same between the different existing health centers is carried out. In this article we will talk about the different types of interoperability, architecture models, the technology used for interoperability and our proposal of interoperability architecture for the RENHICE that complies with what is determined by Law N ° 30024 Creation of the National Registry of Clinical Histories.